Uji Antiseptik Ekstrak Kulit Jeruk Nipis (Citrus aurantifolia) terhadap Bakteri Bacillus cereus dan Escherichia coli - Mirnawati, Mirnawati; Mu’min, Nur; Zahra, Ummi (Al-Kimia, 2021)
Indonesia is one of the countries with the fourth largest natural wealth in the world. The magnitude of the natural potential provides a great opportunity for scientists to develop it as a useful product for society. One of the medicinal plants that can be used is lime (C. aurantifolia). The purpose of this study was to determine the inhibition of lime peel extract (Citrus aurantifolia) against Bacillus cereus, Escherichia coli and mold bacteria using the coloni counter method. This research includes the extraction process of the maceration method then the extract obtained is tested for bacterial analysis using a colony counter. Based on the results of the research conducted, it can be concluded that lime peel extract (C. aurantifolia) has the ability to inhibit the growth of B. cereus and E.coli bacteria, respectively 0 APM/g and <3.0 APM/g. This is because there are bioactive compounds such as -pinene and D-limonene in lime peel extract (C. aurantifolia).